PREVALENCE OF THYROID DYSFUNCTION IN PREVIOUSLY DIAGNOSED DIABETES MELLITUS IN GERIATRIC AND NON-GERIATRIC PATIENTS - RAHUL, RAJESH KUMAR; SENGAR, PUSHPENDRA SINGH; JAIN, ANURAG; SHUKLA, DEVPRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to assess the prevalence of thyroid dysfunction in previously diagnosed diabetes mellitus in geriatric and non-geriatric patients. Methods: The present study was done at a medical college tertiary care center that caters to the needs of a vast amount of population in and around the region of Indore. Results: In the present study, we noted that the thyroid stimulating hormone levels were higher in the older population as compared to the non-geriatric group which was significant p=0.002. In the present study, we noted that the overall mean levels of thyroid stimulating hormone were 3.89 mg/dL standard deviation (SD) + 4.57, in the non-geriatric group, the mean levels of thyroid stimulating hormone were 4.63 mg/dL SD + 5.15 mg/dL and in the geriatric group, the mean levels of thyroid stimulating hormone were 13.15 mg/dL SD + 3.81 mg/dL. In the present study, we noted that the thyroid stimulating hormone levels were higher in the older population as compared to the non-geriatric group which was significant p=0.002. Conclusion: The disease diabetes mellitus has a higher prevalence in males as compared to the females with the male-to-female ratio being (1.57:1), and this trend was same in both the study groups non-geriatric (1.8:1), and geriatric (1.68:1).